Toward the Development of the Trojan Female Technique in Pest Insects: Male‐Specific Influence of Mitochondrial Haplotype on Reproductive Output in the Seed Beetle Acanthoscelides obtectus - Lea Vlajnić; Uroš Savković; Jelena Jović; Sanja Budečević; Biljana Stojković; Mirko Đorđević (Evolutionary Applications)
ABSTRACT Biocontrol techniques that impair reproductive capacity of insect pests provide opportunities to control the dynamics of their populations while minimizing collateral damage to non‐target species and the environment. The Trojan Female Technique, or TFT, is a method of the trans‐generational fertility‐based population control through the release of females that carry mitochondrial DNA mutations that negatively affect male, but not female, reproductive output. TFT is based on the evolutionary hypothesis that, due to maternal inheritance of mitochondria, mutations which are beneficial or neutral in females but harmful in males can accumulate in the mitochondrial genome without selection acting against them. Although TFT has been theoretically substantiated, empirical work to date has focused only on Drosophila melanogaster populations, while the existence of male‐biased mutations and the TFT approach in economically important pest species remain unexplored. Here, we examined the sex‐specific effects of three distinct and naturally occurring mitochondrial haplotypes (MG1a, MG1d, and MG3b) on several reproductive and life history traits in the seed beetle Acanthoscelides obtectus. Our results revealed that males harboring the MG3b mitotype exhibited lower early fecundity and fertility, while there were no effects on females or longevity in either sex. Our experiments provide support for the existence of the mitochondrial variant that specifically impairs male reproductive output in pest insects. These results can be harnessed to further develop TFT as a novel form of biocontrol with broad applicability to economic pests and disease vector insects.